2020
DOI: 10.1111/dom.13993
|View full text |Cite
|
Sign up to set email alerts
|

Clinical use of a 180‐day implantable glucose sensor improves glycated haemoglobin and time in range in patients with type 1 diabetes

Abstract: AimsThis real‐world study evaluated the changes in glycated haemoglobin (HbA1c) and continuous glucose monitoring (CGM) metrics associated with use of the implantable 180‐day Eversense CGM System (Eversense) in patients with type 1 diabetes.Materials and methodsThis was a prospective, multicentre, observational study among adult participants aged ≥18 years with type 1 diabetes across seven diabetes‐care centres in Italy who had Eversense inserted for the first time. HbA1c was measured at baseline and at 180 da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
1
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 20 publications
0
15
1
2
Order By: Relevance
“…Indeed, the TBR (< 70) of patients with type 2 diabetes in our study was very high at 5.6%, but most patients did not feel hypoglycemic. This would explain the higher-thanexpected HbA1c for a TIR of 70% (7.6%) than the 6.9% measured in a previous study (Irace et al 2020). In this regard, the accuracy of readings below the hypoglycemic range was not confirmed in our study given that the FreeStyle Libre Pro does not utilize blood glucose for calibration.…”
Section: Discussioncontrasting
confidence: 82%
See 1 more Smart Citation
“…Indeed, the TBR (< 70) of patients with type 2 diabetes in our study was very high at 5.6%, but most patients did not feel hypoglycemic. This would explain the higher-thanexpected HbA1c for a TIR of 70% (7.6%) than the 6.9% measured in a previous study (Irace et al 2020). In this regard, the accuracy of readings below the hypoglycemic range was not confirmed in our study given that the FreeStyle Libre Pro does not utilize blood glucose for calibration.…”
Section: Discussioncontrasting
confidence: 82%
“…This was inconsistent with the HbA1c level corresponding to a 70% TIR, indicating the difficulty in achieving a 70% TIR without hypoglycemia in patients with type 1 diabetes in this study. This might be due to higher GV, standard deviation, % coefficient of variation, mean amplitude of glycemic excursion, and average daily risk range in the type 1 diabetes group in this study, which highlighted the difficulty and importance of targeting GV in type 1 diabetes if the recommended targets are to be achieved safely (Irace et al 2020;Rodbard 2020). Indeed, our data demonstrated that dissociations between the desired TIR and TBR were observed more frequently in patients with type 1 diabetes who had % coefficients of variation > 36%.…”
Section: Discussionmentioning
confidence: 80%
“…We stratified the study population to 3 groups according to delta-TIR: improved TIR (delta-TIR > 3%), stable TIR (−3% ≤ delta-TIR ≤ 3%) and worse TIR (delta-TIR < -3%). This stratification was based on charts that translate a change in TIR to a clinically significant change in HbA1c [18,19]. Although the difference in TIR is a useful research tool for comparative analysis, consensus regarding a clinically significant difference is lacking [15].…”
Section: Outcome Measuresmentioning
confidence: 99%
“…As a result, the PROMISE study provided further evidence of the safety of the Eversense 180 CGM System, which has been demonstrated in other clinical studies [7][8][9] and real-world evaluation. 10,19,20 Many of the AEs associated with the Eversense 180 CGM system, including with SBA sensors, are common to all CGM systems. However, due to the unique requirement for a minor office-based procedure to insert and remove the sensor, the insertion/removal procedure-related AEs in the PROMISE study, including with the SBA sensor, were minor and similar to that observed in the 90-day US pivotal studies 8,9 and in studies evaluating the present EU Eversense system.…”
Section: Discussionmentioning
confidence: 99%